Analysis of the Costs Associated With the Elective Evaluation of Patients Labelled as Allergic to Beta-Lactams or Nonsteroidal Antiinflamatory Agents - Sobrino-García, Miriam; Moreno, Esther M.; Muñoz-Bellido, Francisco J.; Gracia-Bara, Maria T.; Laffond, Elena; Doña, Inmaculada; Martín, Cristina; Macías, Eva M.; de Arriba, Sonia; Campanón, Valle; Gallardo, Alicia; Dávila, Ignacio (Frontiers in Pharmacology, 2020)
Introduction: Being labeled as allergic to different drugs results in patients receiving other treatments, usually at higher cost, more toxic, and less effective. We aimed to analyze different studies of the costs of drug hypersensitivity assessment. Methods: A bibliographic search on studies regarding this issue was performed, including the available scientific evidence up to June 2020. We searched three databases with terms related to costs and allergy testing in drug hypersensitivity reactions. Results: Our search revealed 1,430 publications, of which 15 met the inclusion criteria. In the manuscript, prospective studies evaluating the costs of the evaluation of patients with suspected allergy to beta-lactams or NSAIDs are analyzed. Also, the costs associated with incorrect labeling as NSAID or penicillin allergy are commented Conclusion: Even considering all possible costs, the evaluation of drug hypersensitivity is not expensive, particularly considering the economic and clinical consequences of labeling a patient with hypersensitivity to drugs.